2022
DOI: 10.1039/d2ta00078d
|View full text |Cite
|
Sign up to set email alerts
|

Lithium insertion in hard carbon as observed by 7Li NMR and XRD. The local and mesoscopic order and their relevance for lithium storage and diffusion

Abstract: We investigate hard carbon fibers at different states of charge by a combination of 7Li-NMR and 2D-XRD. In particular, we record the quadrupole-split 7Li-NMR spectra and 7Li longitudinal relaxation over...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 93 publications
1
5
0
Order By: Relevance
“…This indicates that at increased charge states Li is located in both ordered and disordered domains, while at lower charge states, Li is mainly located in disordered domains. Similar conclusion was drawn by Fang et al using X-ray diffractometry and nuclear magnetic resonance on lithiated carbon fibres [14]. It is important to note that the ordered domains in a carbon fibre have a turbostratic structure instead of a graphitic structure (hexagonal close packed).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This indicates that at increased charge states Li is located in both ordered and disordered domains, while at lower charge states, Li is mainly located in disordered domains. Similar conclusion was drawn by Fang et al using X-ray diffractometry and nuclear magnetic resonance on lithiated carbon fibres [14]. It is important to note that the ordered domains in a carbon fibre have a turbostratic structure instead of a graphitic structure (hexagonal close packed).…”
Section: Resultssupporting
confidence: 83%
“…During delithiation the fibre essentially reverts to its initial state [13]. The techniques -X-ray diffractometry (XRD), nuclear magnetic resonance (NMR) [14], Raman spectroscopy and synchrotron hard X-ray photoelectron spectroscopy (HAXPES)that have been used up until now to study multifunctional carbon fibres, generate global information, which is often based on multiple fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of alkali metal insertion into HC is still under debate, leading studies on HCs as negative electrode materials for Li-or Na-ion batteries suggest that adsorption on defect sites, intercalation into the interlayer of graphite-like domains, and formation of quasi-metallic Li or Na clusters in nanopores occur in the stated order from high to low potential, close to A + /A. 63,[65][66][67][68][69][70][71][72][73][74][75] The formation of quasi-metallic clusters at lower potentials explains why some HC materials exhibit signicantly large Na storage capacities that exceed the stoichiometric composition of NaC 6 . 73 The mechanism by which K is inserted into HC has been less investigated and is less understood than that of the Li and Na systems, and no direct evidence of the formation of quasi-metallic K clusters, as in the case of Li and Na, has been reported, to the best of our knowledge.…”
Section: Electrochemical Rb Insertion Into Amorphous Carbonsmentioning
confidence: 99%
“…While the overall performance of the cell is dependent on a combination of mass-transport, kinetic, and cell-design parameters, it has been found that the fast-charge capability is significantly impacted by physical–chemical phenomena, which are specific to the anode active material upon lithiation. In particular, phase-separation phenomena, where lithiated graphite forms distinct phases, make graphite particularly poor at fast charge in terms of the capacity retained and cell degradation. , Prior works have shown that disordered carbon anodes are well suited for fast charge because they retain high capacity at high charging rates as well as resist Li plating. While there are interesting studies on the intercalation mechanism in disordered carbon, ,, a comprehensive breakdown of the physical processes that explain the differences in performance compared to graphitic electrodes has not been provided to date.…”
Section: Introductionmentioning
confidence: 99%